1999
DOI: 10.1017/s0143385799130177
|View full text |Cite
|
Sign up to set email alerts
|

Positive exponent in families with flat critical point

Abstract: It is known that in generic, full unimodal families with a critical point of finite order, there exists a set of positive measure in parameter space such that the corresponding maps have chaotic behaviour. In this paper we prove the corresponding statement for certain families of unimodal maps with flat critical point. One of the key-points is a large deviation argument for sums of ‘almost’ independent random variables with only finitely many moments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 15 publications
0
23
0
Order By: Relevance
“…The concept of Misiurewicz parameter exists in other contexts too, see [14,6,3,10] for example. The articles [15,30,26,4] all find positive measure sets of non-hyperbolic parameters (indeed one admitting absolutely continuous invariant probability measures) in a neighbourhood of Misiurewicz parameters. On the other hand, Misiurewicz parameters have zero Lebesgue measure, in general ( [29,1,3]).…”
Section: Introductionmentioning
confidence: 99%
“…The concept of Misiurewicz parameter exists in other contexts too, see [14,6,3,10] for example. The articles [15,30,26,4] all find positive measure sets of non-hyperbolic parameters (indeed one admitting absolutely continuous invariant probability measures) in a neighbourhood of Misiurewicz parameters. On the other hand, Misiurewicz parameters have zero Lebesgue measure, in general ( [29,1,3]).…”
Section: Introductionmentioning
confidence: 99%
“…Thunberg, in [33], showed Benedicks-Carleson type results for unimodal families of maps with critical behaviour like exp(−|x| −α ) for α < 1/8. He asked whether for α 1 no acip can exist.…”
Section: Smooth Maps With Flat Topsmentioning
confidence: 97%
“…A first and remarkable observation which was already made as far back as the 1940's by Ulam and von Neumann [30] is that the parameter 2 can be thought of as "stochastic" in a precise mathematical sense (more formally, the corresponding map f a admits an ergodic invariant probability measure which is absolutely continuous with respect to Lebesgue measure). In 1981, Jakobson [6] and then in 1985 Benedicks and Carleson [2], showed that the set Ω + ⊂ Ω of such stochastic parameters is actually "large" in the sense that it has positive Lebesgue measure (see also some generalizations in [24,28,23,20,27,12,13]). Interestingly, however, it is also "small" in the sense that it is topologically nowhere dense, a fact that follows from the remarkable result that the set Ω − ⊂ Ω of "regular" parameters (for which almost every initial condition is eventually attracted to a periodic orbit) is open and dense in Ω [4,15,16] (see also generalizations in [10,11]).…”
Section: Background and Basic Definitionsmentioning
confidence: 99%